Synthesis of Coumarin Derivatives Coupled to Amino Acid Esters and Studying their Biological Activity as Antimicrobial Agents - A. Al-Dawaf, Rana; Y. Saour, Kawkab (Iraqi Journal of Pharmaceutical Sciences, 2017)
A series of coumarin derivatives linked to amino acid ester side chains were synthesized and evaluated of their antibacterial and antifungal activity. The coumarin derivatives was alkylated by the ethyl bromoacetate and then using potassium carbonate to get alkylated hymecromone. Conventional solution method for amide bond formation was used as a coupling method between the carboxy-protected amino acids with acetic acid side chain of coumarin derivatives. The DCC/ HOBt coupling reagents were used for peptide bond formation. The proposed analogues were successfully synthesized and their structural formulas were consistent with the proposed structures as they were proved and characterized by thin layer chromatography (TLC), melting point, infrared spectroscopy (IR), and elemental microanalysis (CHN). Key words: coumarin, amino acid, coumarin antimicrobialal activity.